2013
DOI: 10.1093/annhyg/met025
|View full text |Cite
|
Sign up to set email alerts
|

Intersampler Field Comparison of Respicon<sup>®</sup>, IOM, and Closed-Face 25-mm Personal Aerosol Samplers During Primary Production of Aluminium

Abstract: Intersampler field comparison of Respicon(®), 25-mm closed-face 'total dust' cassette (CFC), and IOM inhalable aerosol sampler was conducted in pot rooms at seven aluminium smelters. The aerosol mass and water-soluble fluoride were selected as airborne contaminants for the comparisons. The aerosol masses of 889 sample pairs of IOM and Respicon(®) inhalable aerosol sub-fraction, 165 of IOM and 25-mm CFC, and 194 of CFC and Respicon(®) thoracic aerosol sub-fraction were compared. The number of sample pairs for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This may be partly due to the orientation of the CFC sampler in which its inlet hole faces downward. This finding is in agreement with results of Görner et al (2010) and Buchan et al (1986) who measured the aspiration efficiency of the CFC sampler at various angles of inclination in a laboratory study as well as with results from Skaugset et al (2013) obtained in a field study carried out in the aluminium industry.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be partly due to the orientation of the CFC sampler in which its inlet hole faces downward. This finding is in agreement with results of Görner et al (2010) and Buchan et al (1986) who measured the aspiration efficiency of the CFC sampler at various angles of inclination in a laboratory study as well as with results from Skaugset et al (2013) obtained in a field study carried out in the aluminium industry.…”
Section: Discussionsupporting
confidence: 91%
“…Many laboratory and field studies carried out in various industrial environments have shown that measurements of inhalable concentrations are generally higher than those made when using the ‘total’ particulate (CFC) method. In the papers of Werner et al (1996) , Davies et al (1999) , and Skaugset et al (2013) , where the IOM sampler was used for inhalable sampling, mean conversion factors from 1.2 up to 4.2 were reported depending on the coarseness of the workplace aerosol monitored. There are also field studies dedicated specifically to Be comparing different sampling methods.…”
Section: Introductionmentioning
confidence: 99%
“…Personal dust samples were taken in the workers breathing zone using 25-mm three piece, closed-faced conductive cassettes (Millipore MAWP 025 AC) with a cellulose acetate filter (Millipore AAWP02500) attached to Side Kick Casella pumps with a flow rate of 2 l min −1 ( Occupational Safety and Health Administration, 2014 ). This sampling head has the same geometry (except for the cassette diameter) and orifice diameter as the 37 mm three-piece cassette used for ‘total’ dust sampling, and has also been assumed to sample ‘total’ dust at a flow rate of 2 l min −1 ( Skaugset et al ., 2013 ). The pumps were paused during lunch breaks.…”
Section: Methodsmentioning
confidence: 99%
“…The IOM dual sampler, which measures both the inhalable and respirable fractions has been used in three publications [ 28 , 29 , 37 ]. In addition, two publications [ 40 , 41 ] have used the Respicon sampler to analyse the inhalable, respirable and thoracic fractions and one publication has used the Respicon sampler to analyse the inhalable and thoracic fractions [ 42 ].…”
Section: Resultsmentioning
confidence: 99%